2015
DOI: 10.1039/c5ta03809j
|View full text |Cite
|
Sign up to set email alerts
|

Rational syntheses of core–shell Fe@(PtRu) nanoparticle electrocatalysts for the methanol oxidation reaction with complete suppression of CO-poisoning and highly enhanced activity

Abstract: We report the syntheses of ternary nanoparticles (NPs) of Fex@(PtRu)(1-x)/2 (x = 0.0, 0.30, 0.34, 0.38, and 0.44) with Fe cores and PtRu alloy shells, which exhibit greatly improved electrocatalytic properties for methanol oxidation reaction (MOR). The syntheses were achieved by one-step sonochemical treatments of Pt(acac)2, Ru(acac)3, and Fe(acac)3 in ethylene glycol. The NPs are characterized by X-ray diffractometry, transmission electron microscopy (TEM), and inductively couple plasma-adsorption emission sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(75 citation statements)
references
References 77 publications
9
66
0
Order By: Relevance
“…5% unreacted Pt(IV). 54 The TEM image (as shown in Fig. S11, ESI †) of Pt/CTF-1-100W shows that the Pt particles are 1-5 nm and highly dispersed , which is 50 times higher than the widely used reference polymer photocatalyst 3 wt%Pt/g-C 3 N 4 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…5% unreacted Pt(IV). 54 The TEM image (as shown in Fig. S11, ESI †) of Pt/CTF-1-100W shows that the Pt particles are 1-5 nm and highly dispersed , which is 50 times higher than the widely used reference polymer photocatalyst 3 wt%Pt/g-C 3 N 4 , as shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The spectrum of Pt 4f ( Figure 4I) also shows two peaks at 72.8 eV (Pt 4f 7/2 ) and 77.1 eV (Pt 4f 5/2 ), indicating the divalent state of metal in M-CQDs. 39,40 The Pd and Pt metal content in the corresponding M-CQDs is measured to be 3.5% and 2.6%, respectively. The XPS spectrum clearly demonstrated that the metals (Pd or Pt) have been successfully embedded into the CQDs through the hydrothermal treatment of related metal complex of TPP.…”
Section: Xps Characterizationmentioning
confidence: 99%
“…In addition, the onset potential of MOR for the resulting PtRuCu 6 -A/C was − 173 mV, presenting a negative shift of 42 and 173 mV as compared with PtRu/C and Pt/C. Here, Matin et al [153] suggested that the good CO tolerance and catalytic activity of PtRu shells originate from both bifunctional mechanisms with the presence of Ru and effects from the core such as compressive strains.…”
Section: Core-shell-structured Catalysts With Alloy Shellsmentioning
confidence: 99%
“…Here, experimental and theoretical data showed that the resulting PtFe 1.2 /C with the highest Fe content and a monolayer Pt shell provided the highest ORR activity. In another example, Matin et al [153] prepared a core-shellstructured Fe@PtRu catalyst using one-step sonochemical reactions that demonstrated enhanced MOR electrocatalytic activities by a factor of up to 2.5 based on I f and improved stability as compared with a commercial PtRu-alloy (PtRu) catalyst, particularly in the complete suppression of COpoisoning. As shown in Fig.…”
Section: Fe As Corementioning
confidence: 99%
See 1 more Smart Citation